(untitled) (Proceedings of International Conference on Special Education, 2019)
The potential of Deaf students can be developed and optimized through the appropriate education. Dancing creation Learning is an alternative educational learning in developing interests, talents, and potential students in the dance sector. Through the school services which has extracurricular art of dance, students are expected to develop their potential optimally. The research purpose is to get a real representation of Dancing creation Learning on deaf students at SLB-B Sukapura Bandung. This research used qualitative approach within case study method. Data collection was done through observation, interview, and documentation during research. Examination Technique of data validity used triangulation technique. Based on results, this research shows the accordance with needs, interests and talents of children during the process of learning program that made. Nevertheless, there is improvement in terms of evaluation needed, the teacher should have to use appropriate evaluation tools based on students needs to know the weaknesses on the learning.